Sytuacja społeczno-polityczna osób niepełnosprawnych1 w III RP - Bilińska, Inez; Ossowski, Szymon (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The paper discusses and illustrates the most significant issues related to the functioning of the disabled in the social and political dimensions. The evolution of social attitudes to people with disabilities over the centuries is shown. The paper discusses the matters of how Poles perceive disability, the solutions in the electoral code and other legal acts and documents, and increasingly frequent social awareness campaigns that are aimed to encourage the disabled to vote in elections, which all have a beneficial impact on the process of activization of the disabled as rightful citizens. The paper is interdisciplinary, encompassing the points of view of a researcher dealing with physiotherapy and that of a researcher into political science, making it unique.